Differences between the evaluation of thermal environment in shaded and sunny position - Kántor, Noémi (Hungarian Geographical Bulletin, 2016)
Great attention has been paid in the last one and a half decade to the subjective evaluation of atmospheric conditions in different outdoor and semi-outdoor urban environments. Several field surveys were conducted all around the world in order to specify those physical and personal factors that influence the perception of thermal environment. Many studies reported about seasonal differences in the subjective assessment concerning thermal sensitivity as well as the so-called neutral temperature. The present investigation aims to reveal these seasonal differences in Hungary and to scrutinise the effect of solar exposure (staying in shaded position or in the sun) on these patterns. The analyses are based on a long-term outdoor thermal comfort project with 78 measurements days conducted on six recreational places in Szeged, Hungary. In the frame of the project thousands of people were asked about their actual thermal sensation and about their preference for any change regarding the thermal environment. Parallel to the questionnaire survey, detailed human bio-meteorological measurements were carried out in the vicinity of the questioned individuals. A well-established human bio-meteorological index was calculated from the measured atmospheric parameters: the Physiologically Equivalent Temperature (PET). Regression analysis was performed between the subjective and objective measures in order to specify neutral and preferred temperatures (nPET, pPET). Furthermore, in the case pPET values a new assignment procedure was also implemented building on probit model technique. The two analytical approaches resulted in very similar pPET values in every case when the sample size was sufficiently large. The study revealed much higher pPET than nPET values in every season; moreover, significant differences depending on the sun exposure of the subjects.